Gut virome-microbiome interactions across hosts and environments - Samson, Rachel; Hassard, Francis; Dharne, Mahesh (NPJ Biofilms and Microbiomes, 2026)
The Gut microbiome-virome dynamics and interactions Collection highlights gut viruses, mainly bacteriophages, as determinants of microbial community structure and host-relevant functions across human, animal, and environmental systems. The Collection welcomes studies that quantify virus-microbe interactions, evidence-based linking viruses to microbial hosts, characterise infection dynamics, and connect them to ecological or clinical outcomes. It prioritises methodological rigour and translational relevance in diagnostics, surveillance, and phage-based interventions.